(untitled) (Research, Society and Development, 2020)
The present study aimed: i) to characterize the performance of different areas in Enem, from an Integrative Review; ii) to compare Physical Education performance in this exam by region, sex gender and type of institution; iii) to relate the items of this component to the Languages and Codes area; and iv) to analyze the psychometric characteristics of Physical Education items. The results have pointed out: a) lack of studies related to the subject, both in the different areas of Enem and in the Physical Education items; b) better performance of students who were from private schools and also from the South and Southeast regions; and c) Physical Education items with difficulty index classified, for the most part, as Easy and Medium, respectively.